2011
DOI: 10.1016/j.ejcts.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of intra-operative device closure of atrial septal defect with transthoracic minimal invasion

Abstract: Intra-operative device closure of atrial septal defect with transthoracic minimal invasion is a safe and feasible technique. It had the advantages of cost savings, yielding better cosmetic results, and leaving less trauma than surgical closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 23 publications
2
41
0
Order By: Relevance
“…Many reports have described the similarities in the complications and long-term prognosis after atrial septal Amplatzer occlusion, interventional occlusion, and surgical occlusion (22)(23)(24); therefore, we have not discussed these details in the present report. Our patients were followed up for 2 years, and no significant adverse events occurred, which is consistent with other studies.…”
Section: Discussionmentioning
confidence: 83%
“…Many reports have described the similarities in the complications and long-term prognosis after atrial septal Amplatzer occlusion, interventional occlusion, and surgical occlusion (22)(23)(24); therefore, we have not discussed these details in the present report. Our patients were followed up for 2 years, and no significant adverse events occurred, which is consistent with other studies.…”
Section: Discussionmentioning
confidence: 83%
“…Meanwhile, another study also confirmed the safety and efficacy of transthoracic echocardiographic guidance of ASD device closure. [28] In our previous papers, [10,27] we also reported our mature experience about using transthoracic echocardiography as the only guiding tool. With the help of the experienced sinologist, the different acoustic view by TTE can provide a satisfactory visualization to guide our operation, which may make the transthoracic procedure more simple.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, we have introduced this domestic device. [10] The device consists of an occluder made from an alloy of nickel and titanium, a metal delivered sheath, and a pushing rod. The double disc occluder has a 10-cm thread in the right disc, facilitating its withdrawal into the 40-cm long and 3 to 6 diameter sheath.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of devices similar to ASO from China but larger than 40 mm showed feasibility of closure of ASD using devices up to 46 mm . These devices were initially deployed by hybrid surgical per‐atrial techniques . Data are scarce on the safety of these devices, especially its impact on erosions, arrhythmias, valvar regurgitation, thrombus formation, and embolization.…”
Section: Introductionmentioning
confidence: 99%